Successional sequence of forest types in a disturbed dry forest reserve in southern Benin, West Africa - Nansen, C.; Tchabi, A.; Meikle, W.G. (Cambridge University Press, 2001)
Human pressure on forest resources in southern Benin has led to a dramatic reduction and disturbance of natural forest patches. The largest remaining forest reserve in southern Benin is the Lama forest, which is known to be a reserve for many endangered species and situated in the boundary between dry forest and savanna. From cluster analysis and hierarchical classification of tree species composition, five forest types were identified in the Lama forest, and ordination techniques were used to determine to what extent these forest types were associated with physiognomic tree characteristics. The geographical position of vegetation plots was used to examine the spatial distribution of the identified forest types. The forest types were interpreted as levels in a successional sequence ranging from either disturbed forest or formerly cultivated farmland to dense forest. Based on the outlined succession sequence it was suggested that reforestation should focus on establishment of Anogeissus leiocarpus, Albizia zygia, Lannea nigritana, Ficus exasperata and Lonchocarpus sericeus as these tree species are associated with the initial forest types.